1967
DOI: 10.4095/100926
|View full text |Cite
|
Sign up to set email alerts
|

Geological reconnaissance, southern Baffin Island, district of Franklin

Abstract: Operation Amadjuak, a helicopter-supported project, completed the geological reconnaissance of that part of Bafin Island that lies south of latitude G6" N and southwest of Cumberland Sound, an area. of about 50,000 square miles. Southern Baffin Island is composed primarily of a wide variety of metamorphic rocks, which on the basis of the few currently available isotopic age determinations, are all part of the Churchill Structural Province. Palaeozoic carbonate and argillaceous carbonate rocks outcrop to the so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

1970
1970
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…The magnetic anomalies in eastern Ungava Bay, therefore, may also relate primarily to changes in magnetization of the Precambrian bedrock, and may reflect variation in depth to this surface only insofar as the lithologic differences responsible for varying magnetization also account for differential erosion of the Precambrian basement. Taylor ( 1969) reported that the major structural elements in the region south and east of Ungava Bay, in both Archean and Proterozoic rocks, trend northwest to north-northwest, and he pointed out that distinctive rock units outcropping on land southeast of Ungava Bay lie on strike with identical rock units mapped on the southwestern coast of Baffin Island (Blackadar 1967). This correlation would appear to be compatible in all respects with the magnetic results considered above.…”
Section: ) Reachedsupporting
confidence: 72%
“…The magnetic anomalies in eastern Ungava Bay, therefore, may also relate primarily to changes in magnetization of the Precambrian bedrock, and may reflect variation in depth to this surface only insofar as the lithologic differences responsible for varying magnetization also account for differential erosion of the Precambrian basement. Taylor ( 1969) reported that the major structural elements in the region south and east of Ungava Bay, in both Archean and Proterozoic rocks, trend northwest to north-northwest, and he pointed out that distinctive rock units outcropping on land southeast of Ungava Bay lie on strike with identical rock units mapped on the southwestern coast of Baffin Island (Blackadar 1967). This correlation would appear to be compatible in all respects with the magnetic results considered above.…”
Section: ) Reachedsupporting
confidence: 72%
“…Marble outcrops are not extensive. They contain more than 85% calcite and no dolomite (Riley, 1960;Blackadar, 1967). Paleozoic limestone crops out on southern Baffin Island, in Foxe Basin and near the head of Frobisher Bay (Jackson and Taylor, 1972).…”
Section: Physiographic Settingmentioning
confidence: 99%
“…On the Hall Peninsula, mapping was completed by Blackadar (1967) and released in digital format by St-Onge et al (2006). The southern part of Hall Peninsula, south of the Chidliak area, was remapped in 2012 (Machado et al 2013), and the Chidliak region is scheduled for bedrock mapping during the summer of 2013.…”
Section: Geological Settingmentioning
confidence: 99%